Titanium Coated with Graphene and Niobium Pentoxide for Biomaterial Applications - Hazel Paloma Reis Corado; Francielly Moura de Souza Soraes; Dyanni Manhães Barbosa; Andreza Menezes Lima; Carlos Nelson Elias (International Journal of Biomaterials, 2022)
Graphene and niobium oxide are used in biomaterial coatings. In this work, commercially pure titanium (cp Ti) was coated with graphene oxide (GO), niobium pentoxide (Nb2O5), and a mixture of both materials (NbGO) by the electrochemical deposition method. The surface morphology, roughness, wettability, and degradation of coated and uncoated samples were analyzed by scanning electron microscopy, interferometry, and contact angle. The results showed that the specimens coated with NbGO (cp Ti-NbGO) showed the highest surface roughness (Ra = 0.64 μm) and were hydrophobic. The contact (θ) angle between water and the surface of uncoated specimens (cp Ti), coated with GO (cp Ti-GO), coated with a mixture with GO and Nb2O5) (cp Ti-NbGO), and coated with Nb2O5 were 50.74°, 44.35°, 55.86°, and 100.35°, respectively. The electrochemical corrosion tests showed that coating with graphene oxide increased the corrosion resistance and coating with Nb2O5 decreased the corrosion resistance. The negative effect of the effect of Nb2O5 coating in corrosion resistance compensated for the release of Nb2O5, which helps osseointegration, increasing cell viability, and proliferation of osteoblasts. The NbGO coating may be a good way to combine the bactericidal effect of graphene oxide with the osseointegration effect of Nb2O5.